Sosialisasi Media Pembelajaran Interaktif Untuk Melatih Keterampilan Abad 21 Sebagai Bentuk Implementasi Kurikulum Merdeka Belajar - Ferry Irawan; Muh. Rafi'y; Dharma Gyta Sari Harahap (Yayasan Perguruan Kampus, 2023)
The learning process is the main key in training students' basic skills completely and comprehensively. Interactive learning media is needed that is able to train students to master every 21st Century skill. One of the interactive learning media that can be used is Kahoot learning media. Through various kinds of complete derivation of features and supported by applicable components so that they can be used in every learning process. The service method used is direct socialization which aims to help teachers recognize and apply interactive learning media. The results of the education show that through Kahoot media students are able to recognize each learning material and teachers can reflect on each learning process through giving quizzes.